Desain Dan Uji Prototipe Alat Pasteurisasi Susu Berbasis Teknologi Irradiasi Ultraviolet (Kajian Dosis Uv) - Lastriyanto, Anang; Kuncahyo, Erry Dwi; Komar, Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
The process of milk pasteurization generally use thermal method. The method can cause microorganisms inactive on the other side, the method result in the degradation of quality food. An alternative method that can be used is by using technology of ultraviolet irradiation. Ultraviolet light has short wavelength with a very strong antimicrobacterialenergy.The mechanism of its wor is by absorbing the energy by nucleid acid without causing damaged on the surface of cel. The absorbed energy will cause the bonding of tymine (dimer tymine) so that the function of nucleic acid is disturbed and it cause the dead of microorganism (Lay and of Hastowo, 1992). The devices used in this research are ultraviolet lamp type C, spiral hose, supporting frame, materials containers and the devices for measuring the amount of microbes, fat, specific gravity and colour. Materials used in this research is fresh milk that obtained from KUD DAU Malang. The result are pasteurization process with UV irradiation decrease microorganisms and fat in milk.Keywords : Pasteurization, ultraviolet irradiation, milk.